Creating Standards Interactions with Arabic script in 12 manuscript cultures - Bondarev, Dmitry; Gori, Alessandro; Souag, Lameen (De Gruyter, 2019)
This book deals with various aspects of standardisation by stepping outside the disciplinary and regional boundaries and providing a typological cross-cultural comparison of standardisation processes in writing traditions influenced by Arabic where different cultures, languages and scripts interact.